Analysis of Students’ Commitment and Attitude towards Mathematics in Secondary School of Dega Woreda, Oromia National Regional State, Ethiopia - Yilfashewa Seyoum Mekuria; Seleshi Demie Alemu; Hulualem Tadesse (Humaniora, 2018)
The purpose of this research was to analyze the magnitude and intensity of student commitment and attitude towards mathematics in secondary schools of Dega Woreda. A single case study with the involvement of 283 students of grade 10 and 12 of Dega Woreda and all mathematics teachers of the respective grades were considered. Purposive and simple random sampling techniques were employed to select the subjects of the study. Questionnaires and interview as tools for the collection of data were used. The findings reveal that students’scholastic performance is a pass mark and yet, it is not up to the expected level. Though students believe to have favorable attitude and commitment towards mathematics, their performance is very low especially on grade 10 and 12 national examinations. This implies that the behavioral (action) aspect of attitude towards mathematics is relatively the most challenging area in learning mathematics. The results indicate that there is no significant mean difference in attitude towards mathematics between male and female and between secondary and preparatory school students. It is suggested that mathematics teachers should apply appropriate methods of teaching, make an ongoing evaluation, and give continuous feedback to the students with the class size reduced to an optimum number of students (40 to 50). Teachers need to motivate and create conditions in which female students can effectively deal with mathematics classes. In this regard, professional women in science and technology fields may be invited to address how they succeeded in their study to build up the self-esteem of female students in mathematics.